ANALYSIS OF MECHANICAL PROPERTIES OF PROTOTYPE OPTICAL PHASE CONDUCTOR FOR TROPICAL CLIMATE CONDITIONS IN INDONESIA - - Solechan; Samsudi Rahardjo; - Rubijanto JP (TRAKSI, 2013)
Marginal areas especially rural communities still lack electrical lighting and telecommunications facilities. To access the electrical and telecommunications networks required huge costs because there is no infrastructure. To overcome this problem the government is targeting the national electrical capacity 57 thousand Megawatts in 2016 by appointing the State Electricity Company. This study makes OPPC cable used for extra high voltage power conductors and internet network data that has reliable performance and durable. These goals will be achieved when the known characteristics and mechanical properties OPPC cable. The results of material testing OPPC cable diameter of 3 cm for Type-voltage torsional twisting 36/6/24 RBS 50% have the impact strength and tensile highest of 112.27 kN and 61.26 MPa. While the impact strength and tensile cables that OPPC least 3 cm in diameter with a voltage selection of the type of 36/6/24 RBS 25% of 63.24 kN and 36.36 MPa. The tensile strength and impact influenced the amount of galvanized steel wire and twisting torsional stress. The more galvanized steel wire and high torsional twisting voltage, proportional to the impact strength and tensile increased. When compared to ACSR cable and commercial OPPC, impact strength and tensile cables made OPPC nearing kekuatanya value, where the tensile strength and impact ACSR cable with voltage torsional twisting RBS 50% by 117 kN and 61.26 MPa and cables for commercial OPPC 116 kN and 63 MPa   Keywords: Aluminium, Wire, Twist, Fiber Optics, Impact Test.